2015
DOI: 10.1186/s13059-015-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

A haplotype map of allohexaploid wheat reveals distinct patterns of selection on homoeologous genomes

Abstract: BackgroundBread wheat is an allopolyploid species with a large, highly repetitive genome. To investigate the impact of selection on variants distributed among homoeologous wheat genomes and to build a foundation for understanding genotype-phenotype relationships, we performed population-scale re-sequencing of a diverse panel of wheat lines.ResultsA sample of 62 diverse lines was re-sequenced using the whole exome capture and genotyping-by-sequencing approaches. We describe the allele frequency, functional sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
228
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(248 citation statements)
references
References 106 publications
(165 reference statements)
20
228
0
Order By: Relevance
“…The ability to query homeologue-specific expression data will also complement growing knowledge about sequence diversity between homeologues. A recent genome-wide analysis between landraces and elite varieties suggested that, during domestication, positive selection was usually restricted to an advantageous mutation within a single homeologue (Jordan et al, 2015). This highlights that understanding of homeologue-specific variation in both sequence and expression will be fundamental for future advances in wheat improvement.…”
Section: Discussion Highly Accurate Pipelinementioning
confidence: 99%
“…The ability to query homeologue-specific expression data will also complement growing knowledge about sequence diversity between homeologues. A recent genome-wide analysis between landraces and elite varieties suggested that, during domestication, positive selection was usually restricted to an advantageous mutation within a single homeologue (Jordan et al, 2015). This highlights that understanding of homeologue-specific variation in both sequence and expression will be fundamental for future advances in wheat improvement.…”
Section: Discussion Highly Accurate Pipelinementioning
confidence: 99%
“…The chip used to genotype the population yielded 9,290 mapped SNPs functional for the GWAS, of which only 11.7% were located on D chromosomes. Even though this might have hampered QTL discovery in these regions, the D genome shows a reduced diversity compared to A and B [42], hence less genetic variation influencing the traits are expected to be found on the D genome.…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to those obtained by Jordan et al (2015) who found that 52.3% of the SNPs were non-synonimous (Jordan et al, 2015). The dataset represents the most comprehensive SNP resource available for the improvement of elite bread wheat cultivars.…”
Section: Snp Discoverysupporting
confidence: 79%
“…Most sequencing projects focus on reference genome assembly and the discovery of SNPs, however, the importance of structural variants is becoming increasingly acknowledged , Jordan et al, 2015. Studies in several plant species reveal the existence of extensive structural variation (Gordon et al, 2014, Xu et al, 2012, Springer et al, 2009b, Hardigan et al, 2016, Li et al, 2014d.…”
Section: Introductionmentioning
confidence: 99%